2012
DOI: 10.1130/b30526.1
|View full text |Cite
|
Sign up to set email alerts
|

Field test of autogenic control on alluvial stratigraphy (Ferris Formation, Upper Cretaceous-Paleogene, Wyoming)

Abstract: Internally generated (autogenic) sedimentary processes can obscure signals of tectonic movements, climate conditions, or sea-level fl uctuations in alluvial basins. The stratigraphic effects of autogenic dynamics have been considered negligible on time scales of 10 4 -10 6 yr. However, recent physical and numerical models have shown that over basin-fi lling time scales, self-organization in sedimentary systems can produce stratigraphic patterns similar to those resulting from changing basin boundary conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…The density of channel‐body clustering is high around the avulsion sites compared to the channel‐body clustering downstream of avulsions (Figure ). Although floodplain deposition of fine sediment was absent in our experiment, these results indicate that the channel‐body clustering may give insight into the location of paleo‐river avulsions in deltaic deposits [e.g., Jerolmack and Paola , ; Hajek et al , ]. Our experimental results of avulsion length scaling with the backwater length (Figure c) also bolster the use of backwater length as a paleohydraulic reconstruction tool [ DiBiase et al , ] where the avulsion length, channel bed slope, and characteristic flow depth are interrelated, i.e., L A ~ L b = h c /S .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The density of channel‐body clustering is high around the avulsion sites compared to the channel‐body clustering downstream of avulsions (Figure ). Although floodplain deposition of fine sediment was absent in our experiment, these results indicate that the channel‐body clustering may give insight into the location of paleo‐river avulsions in deltaic deposits [e.g., Jerolmack and Paola , ; Hajek et al , ]. Our experimental results of avulsion length scaling with the backwater length (Figure c) also bolster the use of backwater length as a paleohydraulic reconstruction tool [ DiBiase et al , ] where the avulsion length, channel bed slope, and characteristic flow depth are interrelated, i.e., L A ~ L b = h c /S .…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, river avulsions present a serious hazard to communities living on deltas worldwide, and understanding their mechanics is vital for sustainable management of deltas, and forecasting deltaic evolution in the face of sea level rise, river engineering, and land use changes upstream of river deltas. From a stratigraphic viewpoint, river avulsions control the distribution of sediment and the stacking patterns of channel bodies in the subsurface [e.g., Allen , ; Bridge and Mackey , ; Mackey and Bridge , ; Mohrig et al , ; Hajek et al , ], and thus are of significant importance for unraveling the mechanics of ancient deltaic systems [e.g., Paola , ; Kleinhans , ; Bianchi and Allison , ; DiBiase et al , ], and for characterization of aquifers and hydrocarbon reservoirs [ Bohacs and Suter , ; Ainsworth et al , ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avulsion “set up” arises where a spatial decrease in water surface slope reduces sediment transport capacity, thus producing a spatial convergence in sediment flux and concomitantly generating in‐channel sediment deposition [ Mohrig et al ., ]. The avulsion “trigger” is typically an event whereby water flow leaves the channel (e.g., overbank flooding) and/or where erosion induces a levee‐breach, during floods [e.g., Edmonds et al ., ; Hajek et al ., ]. While triggers are typically associated with flood events, the antecedent processes are critical to influencing the location and frequency of avulsions.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of the procedure is limited by our understanding of the forward processes, which controls the quality of the probability assigning step (equation ). For instance, only in recent decades has the community started to realize that not all changes in the deposits D B need to incorporate changes in the received signal S A ′ based on field investigations (Beerbower, ; Hajek et al, ; Lewin, ) and flume experiments (Muto & Steel, ; Van Dijk et al, ). For example, the retreat of the Brent Delta was originally interpreted as a result of a reduction in sediment input or increased subsidence (Helland‐Hansen et al, , ); but more recently it has been shown that constant sediment supply and steady relative sea‐level rise could result in the same overall stratal geometry (Muto & Steel, ).…”
Section: Discussionmentioning
confidence: 99%